2016
DOI: 10.1063/1.4959552
|View full text |Cite
|
Sign up to set email alerts
|

Light induced suppression of Kondo effect at amorphous LaAlO3/SrTiO3 interface

Abstract: We report photoelectric properties of two-dimensional electron gas (2DEG) at an amorphous LaAlO3/SrTiO3 interface. Under visible light illumination (650 nm), an enhancement of electric conductivity is observed over the temperature range from 2 to 300 K. Particularly, a resistance upturn appearing below 25 K, which is further proved to from the Kondo effect, is suppressed by the 650 nm visible light. From the results of light-assisted Hall measurements, light irradiation increases the carrier mobility rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The Kondo upturn can be suppressed by light [402,403], even with sub-bandgap excitation of 650 nm [403]. The suppression of the Kondo effect has been attributed to light-induced charge redistribution [402] and destruction of Kondo coherence [403,404].…”
Section: Kondo Effectmentioning
confidence: 99%
“…The Kondo upturn can be suppressed by light [402,403], even with sub-bandgap excitation of 650 nm [403]. The suppression of the Kondo effect has been attributed to light-induced charge redistribution [402] and destruction of Kondo coherence [403,404].…”
Section: Kondo Effectmentioning
confidence: 99%
“…[30] A p-n junction is found to form at the interface of p-type a-C and n-type Q2DEG. Although an electron gas based on the STO surface has been extensively studied since the finding of Hwang et al in 2004, [31][32][33][34] a p-n junction between an electron gas on an STO surface and a p-type semiconductor is successfully achieved for the first time in this work. It is noted that the contact area of p-and n-type materials is nanoscale for the migration of electrons and holes.…”
Section: Resultsmentioning
confidence: 83%
“…It was proposed that the coherence between the localized spin centers was minimized by the light irradiation thus suppressing the Kondo effect. Concomitant with this suppression of the Kondo effect by light illumination, the mobility at the interface was enhanced from ≈50 cm 2 V −1 s −1 without light irradiation to 125 cm 2 V −1 s −1 while the carrier density was unchanged at a temperature of 2 K …”
Section: Light/matter Interactionmentioning
confidence: 96%
“…Later, in LaAl 1− x Ni x O 3 /STO, it was found that the Kondo effect could be enhanced by increasing the Ni level from x = 0 to 0.05 as the dopants provided localized spin centers, but after light irradiation this effect was also reduced . Similarly, the Kondo effect was also found to be suppressed under the visible light of 650 nm in amorphous‐LAO/STO . It was proposed that the coherence between the localized spin centers was minimized by the light irradiation thus suppressing the Kondo effect.…”
Section: Light/matter Interactionmentioning
confidence: 99%